Meningkatkan Keterampilan Menulis Puisi Melalui Penerapan Project Based Learning Pada Siswa Kelas V SD Negeri 1 Tataaran - Julia Tangkilisan; Non Norma Monigir; Widdy H.F Rorimpandey (STAI AL-AMIN, 2026)
This study aims to improve poetry writing skills through the implementation of the Project Based Learning model for fifth-grade students at SD Negeri 1 Tataaran. Based on the results of the initial observations conducted by the researcher, it was found that the students’ poetry writing skills were still low. Out of 24 students, only 5 students or 20.83% achieved learning mastery, while 19 students or 79.17% had not yet achieved mastery.The research method used was Classroom Action Research (CAR), which was conducted in two cycles. This research was carried out through four stages: the planning stage, which involved preparing learning tools, determining project themes, and designing project-based learning activities; the implementation stage, which involved applying the Project Based Learning model in poetry writing activities; the observation stage, which involved observing teacher and student activities during the learning process; and the reflection stage, which involved evaluating the learning outcomes to improve weaknesses in the next cycle. The subjects of this study were 24 fifth-grade students at SD Negeri 1 Tataaran. Data collection techniques were conducted through observations of teacher and student activities as well as poetry writing skill tests. The data analysis technique used was descriptive quantitative analysis. The results of the study showed that in Cycle I, the average student score reached 70 with a learning mastery level of 54.16%. After improvements were made in Cycle II through more intensive guidance, strengthening students’ understanding of the elements of poetry, and increasing student participation in project activities, the average student score increased to 88.96, showing an improvement of 18.96 points or 27.08%. The learning mastery level also increased from 54.16% to 91.66%, showing an improvement of 37.5%. In addition, teacher and student activities during the learning process also improved and reached a very good category. Based on the results of the study, it can be concluded that the implementation of the Project Based Learning model was effective in improving the poetry writing skills of fifth-grade students at SD Negeri 1 Tataaran.